Philippe Descola (Colégio de França) e Tim Ingold (Universidade de Aberdeen) – dois vultos maiores da antropologia contemporânea - Jorge, Vítor Oliveira (Trabalhos de Antropologia e Etnologia, 2020)
The author aims, in a synthetic and non-exhaustive way, to understand some similarities and differences between the programmatic proposals of these two great contemporary anthropologists, showing the problematic framework in which each one of them is inserted. The text have some repetitions, typical of orality, given the fact that it was first presented as a lecture, in which such repetitions are normal and indispensable.